2018
DOI: 10.1371/journal.pntd.0006558
|View full text |Cite
|
Sign up to set email alerts
|

Multi locus sequence typing of Burkholderia pseudomallei isolates from India unveils molecular diversity and confers regional association in Southeast Asia

Abstract: ObjectivesBurkholderia pseudomallei, the causative agent for melioidosis, has become a public health problem in India and across the world. Melioidosis can be difficult to diagnose because of the inconsistent clinical presentations of the disease. This study aims to determine the genetic diversity among the clinical isolates of B. pseudomaelli from India in order to establish a molecular epidemiology and elucidate the Southeast Asian association.MethodsMolecular typing using multi locus sequence typing was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Recently, association of Indian B . pseudomallei isolates with Southeast Asian isolates have been reported by others as well [ 20 ].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Recently, association of Indian B . pseudomallei isolates with Southeast Asian isolates have been reported by others as well [ 20 ].…”
Section: Discussionmentioning
confidence: 60%
“…Only 18 Indian STs were found to be singleton and were outliers. These singleton STs also included ST300 which was reported to be group founder in above study [ 20 ]. Topology and grouping of all Indian STs with other Asian and Australian STs by MEGA showed that majority of Indian isolates grouped together in one large group, however few STs were distant and unique particularly ST1636.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is unknown if diverse genotypes differ in virulence, which might influence successful infection. This clinical isolate was belonged to ST99 which was previously reported in human in Philippines, Thailand, Malaysia and Bangladesh [36, 37]. ST99 was one of the most common stain in Taiwan, found in 24.7% (48/194) of clinical isolates collected during 2004 to 2010 [38].…”
Section: Discussionmentioning
confidence: 71%
“…ST99 was one of the most common stain in Taiwan, found in 24.7% (48/194) of clinical isolates collected during 2004 to 2010 [38]. In Thailand, ST99 was recovered from two soil samples and clinical specimens of two patients in Ubon Ratchathani, Northeast Thailand and in a patient in Songkhla province located in South Thailand [36]. The widespread dissemination distribution of this strain indicated that B .…”
Section: Discussionmentioning
confidence: 99%